MicroRNA-Mutant P53 Crosstalk in Chemoresistance: A Hint to Monitor Therapy Outcome - Speciale, Andrea; Monti, Paola; Fronza, Gilberto; Izzotti, Alberto; Menichini, Paola (MicroRNA, 2020)
The chemoresistance of cancer cells is a multifactorial mechanism in which de-regulated apoptotic pathways, the oxidative response and cancer cell migration play a crucial role. A key player in the control of such pathways is the tumor suppressor gene TP53, also defined as the “guardian of the genome”, encoding the P53 tetrameric transcription factor. P53, following cell injuries, can activate the transcription of several target genes crucial for the induction of apoptosis, cell cycle arrest, modulation of senescence, DNA repair, autophagy and metabolism. Importantly, TP53 gene is mutated in nearly 50% of human cancers, implying an altered expression of target genes in cancer cells. The presence of TP53 mutations can also affect the expression of several small noncoding RNAs (microRNAs or miRNAs) involved in the same regulation of the apoptotic signaling, cell cycle regulation and cell migration. In mutant P53 expressing tumors, some miRNAs resulted in being down-regulated, while others appeared to be up-regulated as demonstrated by in vitro and in vivo studies. Thus, the expression level of specific P53 responsive miRNAs could be used as a marker of cancer progression and therapy performance. In the present review, we will summarize the role of P53-related miRNAs and their clinical relevance in monitoring therapy outcome and progression of cancers with mutant P53.
Keywords: Cancer